2010
DOI: 10.1177/070674371005501203
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and Cancer: In 2010 Do We Understand the Connection?

Abstract: In recent years, there has been a plethora of cancer mortality and incidence data reported in schizophrenia. Despite this, there has been little focus on cancer in schizophrenia guidelines. Additionally, there have been suggestions that schizophrenia may provide inherent protection against cancer. The goal of this review is to establish, using recent data, the incidence and mortality rates for cancer in schizophrenia. Method: We identified systematic reviews and meta-analyses and undertook a search using the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 39 publications
2
52
1
Order By: Relevance
“…Although lung cancer occurs less frequently in patients with schizophrenia than among the general population, the effects of cigarette smoking are clearly seen here [27]. In the case of COPD and lung cancer, cigarette smoking is undoubtedly a significant etiologic factor [28].…”
Section: Health Consequences Of Smoking In Schizophrenicsmentioning
confidence: 89%
“…Although lung cancer occurs less frequently in patients with schizophrenia than among the general population, the effects of cigarette smoking are clearly seen here [27]. In the case of COPD and lung cancer, cigarette smoking is undoubtedly a significant etiologic factor [28].…”
Section: Health Consequences Of Smoking In Schizophrenicsmentioning
confidence: 89%
“…5,7,8 Support for the former comes from the finding that CRC incidence is also reduced in first-degree relatives of people with schizophrenia. 5,6 However, these findings are not universal. One study 9 reported a significantly elevated risk of CRC in patients with schizophrenia that increased further in patients receiving antipsychotics.…”
Section: Limitationsmentioning
confidence: 99%
“…5 Psychiatric patients may also present later because of reduced access to primary care or cancer screening, and therefore have more advanced disease on diagnosis. [10][11][12] There is little information on access to specialist services following diagnosis.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly the data on bone fractures (Howard et al, 2007;Abel et al, 2008) has shown us the potential. The World Health Organization (WHO) initiated a number of databases to measure cancer rates in schizophrenia in the 1970s (Bushe and Hodgson, 2010) and have the knowledge and ability to conduct similar projects worldwide relating to outcomes of hyperprolactinaemia. 3.…”
Section: Hyperprolactinaemia In Children and Adolescentsmentioning
confidence: 99%